Bond behavior and interfacial micro-characteristics of magnesium phosphate cement onto old concrete substrate. (10th April 2018) - Qin, Jihui; Qian, Jueshi; You, Chao; Fan, Yingru; Li, Zhen; Wang, Hongtao
Highlights: The effect of M/P and w/c on the bonding properties of MPC pastes was studied. Interfacial micro-characteristics of MPC and OPC substrate were investigated. Bond mechanism between MPC and OPC substrate was characterized. Abstract: In several applications of magnesium phosphate cement (MPC), one encounters a need for bonding old Portland cement (OPC) concrete with MPC. The bonding characteristics between MPC and OPC concrete substrate, were evaluated using flexural and tensile bond strength, failure modes, scanning electron microscopy (SEM) and X-ray diffraction (XRD). The experimental results show that samples having a lower magnesia to phosphate molar ratio (M/P) and water to cement mass ratio (w/c) exhibit higher bond strength and stronger affinity for OPC concrete, as well as better developed interfacial microstructure. Multiple interfacial interactions between MPC and OPC concrete are evidenced by microstructural analysis and XRD: MPC paste can infiltrate into the irregularities of the OPC substrate; etching of the surface of hardened OPC paste occurs under the pH condition of MPC paste; penetration of soluble phosphate creates the potential for the chemical reaction and filling effect at the interface.